2013
DOI: 10.1615/interfacphenomheattransfer.2013006655
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Thin Liquid Films Falling Down Isothermal and Nonisothermal Walls

Abstract: This paper reviews important results found in the past years on thin films falling down isothermal and nonisothermal walls. The discussion on isothermal flows is presented as the basis and background for the study of nonisothermal flows. Different model equations are presented and their approximations are discussed. Both linear and nonlinear results are surveyed on uniform and nonuniform heating of the wall. Also a review is given of the effect the curvature of the wall has on flows down vertical cylinders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(13 citation statements)
references
References 224 publications
(253 reference statements)
0
13
0
Order By: Relevance
“…The results of this paper are new not only because of the combination of viscoelasticity [37] and thermocapillarity [31] in flow on the surface of a cylinder, but also because the problem investigated is three dimensional. This can be seen in the review section on thin film flow down cylinders presented in Dávalos-orozco [17]. It is found that in the linear and non linear problems, mainly axial mode stability is investigated.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…The results of this paper are new not only because of the combination of viscoelasticity [37] and thermocapillarity [31] in flow on the surface of a cylinder, but also because the problem investigated is three dimensional. This can be seen in the review section on thin film flow down cylinders presented in Dávalos-orozco [17]. It is found that in the linear and non linear problems, mainly axial mode stability is investigated.…”
Section: Introductionmentioning
confidence: 93%
“…When a fluid layer flows down a wall, the thermocapillary effects are included by Joo et al [16,14] and Ramaswamy et al [15]. A complete review of this problem is found in Dávalos-orozco [17].…”
Section: Introductionmentioning
confidence: 99%
“…There are some exceptions, as follows. [34,35] study linear stability properties and nonlinear evolution of a thin film flowing down an inclined heated wall and take into account the thermal conductivity and thickness of the wall. These studies are performed entirely within the context of a Benney-type equation, which has severe limitations as noted above.…”
Section: Introductionmentioning
confidence: 99%
“…The films considered are, therefore, always hydrodynamically stable; the issue of finite-time blow-up of Benney-type equations is thus avoided, but the equation cannot be used to analyze the effects of the conjugate heat transfer on the development of solitary pulses, which only exist for supercritical Reynolds numbers. Similarly to [34,35], the timescales of crossstream thermal diffusion in the liquid and the substrate are taken to be small enough so that the temperature profile in the film and the substrate is slaved to the local film thickness. In [37], this study is extended to include the regime in which the timescale of cross-stream thermal diffusion within the substrate can no longer be neglected, so that the temperature profile is not determined (to leading order) by the film thickness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation